Mott transition in hardcore Bose Hubbard model for honeycomb lattice - Yonathan, Priambada (2015)
The purpose of this study is to learn how to use direct loop update Stochastic Series Expansion Quantum Monte Carlo simulation to observe Mott transition for a hard core bosonic system in a honeycomb lattice using a Bose-Hubbard model. Lattice occupancy is set at 1/2, and the simulation is run on 3 different lattice size, namely for L=4,6, and 8. During the simulation, the transition of the stiffness of the system is measured against the iterating parameter t/V, where t is the amplitude of the hopping component and V is the amplitude of the nearest neighbour potential. The critical point of the transition is then approximated from the intersection of the 3 transition curves.